2019
DOI: 10.1111/crj.13077
|View full text |Cite
|
Sign up to set email alerts
|

Pleural dye marking of lung nodules by electromagnetic navigation bronchoscopy

Abstract: Introduction: Electromagnetic navigation bronchoscopy (ENB)-guided pleural dye marking is useful to localize small peripheral pulmonary nodules for sublobar resection. Objective: To report findings on the use of ENB-guided dye marking among participants in the NAVIGATE study. Methods: NAVIGATE is a prospective, multicentre, global and observational cohort study of ENB use in patients with lung lesions. The current subgroup report is a prespecified 1-month interim analysis of ENB-guided pleural dye marking in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This requires the organization within multiple specialists and facilities, with potential waste of time, resources, delay in complication's management and discomfort for the patient. Some explorative studies have already evaluated the use of ENB to perform preoperative marking (16)(17)(18)(19)(20)(21)(22)(23). In the current study ENB-guided pleural dye marking as preoperative localization of small, pulmonary, highly suspected malignant lesions result feasible.…”
Section: Discussionmentioning
confidence: 81%
“…This requires the organization within multiple specialists and facilities, with potential waste of time, resources, delay in complication's management and discomfort for the patient. Some explorative studies have already evaluated the use of ENB to perform preoperative marking (16)(17)(18)(19)(20)(21)(22)(23). In the current study ENB-guided pleural dye marking as preoperative localization of small, pulmonary, highly suspected malignant lesions result feasible.…”
Section: Discussionmentioning
confidence: 81%
“…Bowling et al recently reported that ENB-guided transbronchial dye marking procedure was regarded as sufficient for surgical resection in 91.3% cases in a large scale prospective cohort study. 15 Cho et al also used ENB-guided dye markings for 32 lesions in 25 patients to localize pulmonary nodules and achieved an 87.5% success rate. 24 Meanwhile, ENB-guided transbronchial approach has a relatively low incidence rate of procedure-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, most previous studies have reported results for patients with only a single lung nodule, and data on the simultaneous resection of multiple lung nodules using ENB-guided localization are scarce. 13,15 In this study, we aimed to validate the accuracy and safety of preoperative ENB-guided transbronchial dye localization for VATS resection of multiple subsolid pulmonary nodules suspected of lung cancer. Furthermore, we also investigated follow-up results regarding changes in lung function after resections of multiple lung nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Bowling et al performed a sub-group analysis of the dye-marking group in the USA cohort of the NAVIGATE study [ 31 ]. Among the patients, 23 subjects (24 lesions) underwent dye marking as a preparation for surgical resection.…”
Section: Electromagnetic Navigation Bronchoscopymentioning
confidence: 99%